2023
DOI: 10.1111/aec.13274
|View full text |Cite
|
Sign up to set email alerts
|

Increased herbivory but not cyanogenesis is associated with urbanization in a tropical wildflower

Abstract: Urbanization is associated with numerous changes to the biotic and abiotic environments, many of which lead to a loss of biodiversity. Some studies have documented increased herbivory rates in cities, which has been hypothesized to lead to the evolution of novel defence traits in plants. Yet evidence supporting this hypothesis is contradictory and entirely absent from South American cities. To address this research gap, we evaluated herbivory rates in the native urban wildflower, Turnera subulata (Turneraceae)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
2
1
Order By: Relevance
“…In the higher latitude, herbivory pressure was smaller than in the lower latitude. Regardless of the latitude, an increase in HPD was not associated with different levels of herbivory across any type of herbivory which disagree with other studies in herbivore abundance (Dale & Frank, 2017;Meineke et al, 2013;Parsons & Frank, 2019) or leaf defoliation (Cuevas-Reyes et al, 2013;Rivkin & de Andrade, 2023). We explain our absence of effects of HPD on herbivory with the counter effects of biotic and abiotic factors occurring in urban areas.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…In the higher latitude, herbivory pressure was smaller than in the lower latitude. Regardless of the latitude, an increase in HPD was not associated with different levels of herbivory across any type of herbivory which disagree with other studies in herbivore abundance (Dale & Frank, 2017;Meineke et al, 2013;Parsons & Frank, 2019) or leaf defoliation (Cuevas-Reyes et al, 2013;Rivkin & de Andrade, 2023). We explain our absence of effects of HPD on herbivory with the counter effects of biotic and abiotic factors occurring in urban areas.…”
Section: Discussioncontrasting
confidence: 98%
“…Besides, other authors have found a decrease in herbivory with the increase in human population either with a decrease in chewer herbivory (Meineke et al, 2019), chewer, leaf miner and galler herbivory (Valdés-Correcher et al, 2022) or for chewer herbivory but not in other guilds (Moreira et al, 2019;Nuckols & Connor, 1995). Contrarily, other studies found an increase in herbivory abundance (Dale & Frank, 2014;Parsons & Frank, 2019) or intensity in chewer herbivory in urban areas (Christie & Hochuli, 2005;Cuevas-Reyes et al, 2013;Rivkin & de Andrade, 2023).…”
Section: Introductionmentioning
confidence: 93%
“…Despite widespread support for the ‘increasing disturbance’ hypothesis, some studies have also reported a positive effect of urbanization on herbivory in different parts of the world, including Brazil (Cuevas‐Reyes et al., 2013; Rivkin & de Andrade, 2023), Australia (Christie & Hochuli, 2005) and the USA (Cregg & Dix, 2001; Dale & Frank, 2017). Likewise, predation by birds and arthropods has been shown to increase across disturbance gradients in the Philippines (Posa et al., 2007) and in Europe (Kozlov et al., 2017).…”
Section: Introductionmentioning
confidence: 99%